Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007906.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Intensive case management for severe mental illness

Abstract: Background Intensive Case Management (ICM) is a community based package of care, aiming to provide long term care for severely mentally ill people who do not require immediate admission. ICM evolved from two original community models of care, Assertive Community Treatment (ACT) and Case Management (CM), where ICM emphasises the importance of small caseload (less than 20) and high intensity input. Objectives To assess the effects of Intensive Case Management (caseload <20) in comparison with non-Intensive Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(112 citation statements)
references
References 328 publications
(228 reference statements)
5
102
0
5
Order By: Relevance
“…length of hospital stays) and costs can often demonstrate significant skew because many patients report low costs, but a small proportion can have disproportionately high levels of use. In line with other published reviews, 26,71 we identified all outcomes where the SD multiplied by two was greater than the mean, as in these cases it is argued that the mean is not a good indicator of the centre of the distribution. 72 When studies reported multiple comparisons that were eligible for the same meta-analysis (e.g.…”
Section: Data Preparation and Analysissupporting
confidence: 75%
“…length of hospital stays) and costs can often demonstrate significant skew because many patients report low costs, but a small proportion can have disproportionately high levels of use. In line with other published reviews, 26,71 we identified all outcomes where the SD multiplied by two was greater than the mean, as in these cases it is argued that the mean is not a good indicator of the centre of the distribution. 72 When studies reported multiple comparisons that were eligible for the same meta-analysis (e.g.…”
Section: Data Preparation and Analysissupporting
confidence: 75%
“…Allerdings entstehen durch das aufwendige Setting vergleichsweise hohe Kosten, sodass vor allem Patienten mit häufigen stationären Aufnahmen (>50 Tage pro Jahr) profitieren [24] und das ACT aus gesundheitsökonomischer Perspektive folglich nicht für Patienten mit seltenen Krankenhausaufenthalten empfohlen werden kann [15]. Ferner bietet sich ACT vor allem in Ballungszentren, weniger in ländlich geprägten einwohnerschwachen Regionen an [3], wenngleich für den ländlichen Raum z.…”
Section: Assertive Community Treatmentunclassified
“…Im Cochrane-Review zum ICM [15] wurden schließlich ACT-und CM-Ansätze unter dem Begriff des Intensive Case Management subsumiert, solange der Betreuungsschlüssel kleiner als 1:20 war, was jedoch keinen allgemeingültigen Konsens darstellt [48].…”
Section: » In Der Praxis Kommt Es Zu üBerschneidungen Der Modelleunclassified
“…Case managers have caseloads of about 20 patients or less, direct contact with patients (Burns et al, 2007) and are clinicians in charge of providing comprehensive treatment, rehabilitation and support services (Scott & Dixon, 1995) together with their CM responsibilities (Marshall, 2008). ICM models aim to maintain patient contact with services, decrease hospital admissions and enhance results (Dieterich, Irving, Park, & Marshall, 2010). Non-ICM models include most of the features of ICM models but a caseload size of over 20 patients.…”
Section: Case Management Modelsmentioning
confidence: 99%
“…This may be related to the fact that they used a meta-analytical approach, which has been considered to provide a more objective assessment of evidence than literature reviews, a more accurate estimate of treatment effect, and may help to better explain inconsistencies between outcomes of individual studies (Egger, Smith, & Phillips, 1997). Together with the above-mentioned Cochrane reviews, there are other reviews that use the same approach in an effort to establish CM efficacy/ effectiveness and, moreover, the Cochrane group has updated its two meta-analytic reviews (Dieterich et al, 2010). Below, there is a description of the main characteristics and results of the meta-analytic reviews conducted to establish the efficacy of CM from 1995 to 2010 (see Table 2).…”
Section: The Effects Of CM Through Meta-analytic Analysesmentioning
confidence: 99%